EFEKTIFITAS PENYELESAIAN SENGKETA WARISAN MELALUI MAJELIS ADAT ACEH (STUDI DI KECAMATAN DARUSSALAM, KABUPATEN ACEH BESAR) - RAHMAT FITRAH (PREMISE LAW JURNAL, 2016)
Judicially, there are types of settling a dispute case: by litigation in the court and by non-litigation outside of the court. In non-litigation as an alternative settling. In Aceh Besar, a dispute is dominantly settled through Majelis Adat (Adat Council) like a problem of inheritance because the people think that it is in accordance with the people’s sense of justice which is more effective. It is, therefore, interesting to analyze is how far the effectiveness of settling a dispute in inheritance the Majelis Adat is. It was located in Darussalam Subdistrict. The result of the research showed that the legal ground for Majelis Adat Aceh Besar in settling dispute in inheritance by handing down the Verdict No. 40/1999 on Organization of Aceh Special Region in which Aceh and Law No. 11/2006 on Aceh Provincial Government. The role of Majelis Adat Aceh Besar in settling dispute in inheritance is a mediator and as a communicator. The implementation of the ruling of the Majelis Adat Aceh Besar in settling dispute in inheritance for the conflicting parties was effective since it is carried out by the stakeholders so that it can be settled by adat (custom) without any conflict in the future. Keywords: Effectiveness, Dispute in Inheritance, Majelis Adat Aceh